Nutritional evaluation of children with phenylketonuria - Fisberg, Regina Mara; Silva-Fernandes , Maria Eugênia da; Schmidt, Benjamim José; Fisberg, Mauro (São Paulo Medical Journal, 1999)
CONTEXT: Dietary phenylalanine (PA) restriction is the most effective form for reducing its excess in the blood and is the only efficient method for treating phenylketonuria. The diet is complex and should be adapted to combine the patients' eating habits, growth and development. It depends basically on the use of industrialized products as substitutes free of PA for proteins that are not fully supplied. OBJECTIVE: To evaluate the nutritional status of children with phenylketonuria (PKU) by anthropometric measurements and food intake. DESIGN: Cross-sectional study. SETTING: Children with PKU attending the Association of Parents and Friends of Handicapped Children (Associação de Pais e Amigos dos Excepcionais - APAE) and normal children attending at municipal day care centers in São Paulo. PARTICIPANTS: 42 children with PKU and 31 normal children aged 1 to 12 of both sexes were assessed in two groups, under and over 7 years of age. MAIN MEASUREMENTS: Weight and height measurements. RESULTS: Children with PKU ingested calories, calcium, iron, zinc, and copper below the recommended values, whereas the protein intake was within the normal range. Food intake in the group of normal children was within normality rates. The height/weight Z-score means for children with PKU were 0.47 for those under 7 years and 1.86 for 7 year-olds and over; in normal children the means were 0.97 <7 years and 1.54 ³7 years, with no statistically significant difference. The height/age Z-score means were significantly lower in the PKU children <7 years (-1.23) than in the normal controls (0.91). CONCLUSIONS: The data presented demonstrate the importance of nutritional surveillance in patients with PKU so as to support adequacy of nutrient intake and to guarantee growth within the relevant standards.